The influence of environments on the epistatic effects of genes controlling some traits in winter rye. - Śmiałowski, Tadeusz; Węgrzyn, Stanisław (Plant Breeding and Seed Science, 2003)
The aim of the study was to show epistatic effects of genes responsible for inheritance of important morphological traits in winter rye populations. Furthermore, the thesis that the environment plays very important role in epistatic effects in winter rye populations was verified. The study showed very significant epistasis for inheritance of the important yield components in 1985-1999 years. It was confirmed that epistasis increased or reduced values of the traits under study. It was also showed that epistasis depended on investigated varieties and environments (year of the study). The method described by Comstock and Robinson (1952), and Kearsey and Jinks (1968) consisting in crossing of selected populations with three different testers: T1 (SMH-49), T2 (SMH-75) and T3 (hybrid T1 × T2) was used. The obtained F1 hybrids were sown in 3-replications every year (1985-1999). The epistatic effects were estimated according to formula; Ji = L1i + L2i – 2L3i, where Ji is the epistatic effects of i-th variety, L1i, L2i, 2L3i are the mean values of characters for the hybrids obtained from the crossing between i-th variety and tester. The study concerned following traits: plant height, heading date, length of ear and uppermost internode of ear, grain yield per ear, grain number per ear, 1000-grain yield, grain yield per plot, test weight, falling number, protein content, resistance to brown rust and powdery mildew. Relationships between epistatic effects for selected traits and precipitation and temperature coefficient were evaluated according to Spearman coefficient of correlation.